2005
DOI: 10.1262/jrd.51.69
|View full text |Cite
|
Sign up to set email alerts
|

Attempt at In Vitro Maturation of Minke Whale (Balaenoptera Bonaerensis) Oocytes Using a Portable CO2 Incubator

Abstract: Abstract. The present study was conducted to investigate whether a portable CO2 incubator was effective for in vitro maturation (IVM) of bovine, porcine and minke whale oocytes, and the effect of maturation media supplemented with different hormones; porcine follicle stimulating hormone (pFSH), estradiol-17β (E2), or pregnant mare's serum gonadotropin (PMSG): human chorionic gonadotropin (hCG) for minke whale immature oocytes was also examined. In vitro maturation rates of bovine and porcine oocytes cultured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…56: [131][132][133][134][135][136][137][138][139] 2010) esearch on in vitro maturation (IVM), in vitro fertilization (IVF), somatic cell nuclear transfer (SCNT) and in vitro culture (IVC) of whale embryos will greatly contribute to our basic understanding of whale reproductive physiology, resulting, ideally, in the application of various assisted reproductive technologies (ARTs) to increase the population and aid in management of cetaceans. Several studies on ARTs with respect to IVM [1][2][3][4][5][6], cryopreservation of oocytes [2,5,7], IVF [3,8], intracytoplasmic sperm injection (ICSI) [5,6,9] and interspecies SCNT [10] have been conducted in Common minke (Balaenoptera acutorostrata) and Antarctic minke (B. bonaerensis) whales. Recently, we attempted for the first time to produce embryos of sei (B. borealis) whales by IVF of IVM oocytes in a research based ship [11].…”
mentioning
confidence: 99%
“…56: [131][132][133][134][135][136][137][138][139] 2010) esearch on in vitro maturation (IVM), in vitro fertilization (IVF), somatic cell nuclear transfer (SCNT) and in vitro culture (IVC) of whale embryos will greatly contribute to our basic understanding of whale reproductive physiology, resulting, ideally, in the application of various assisted reproductive technologies (ARTs) to increase the population and aid in management of cetaceans. Several studies on ARTs with respect to IVM [1][2][3][4][5][6], cryopreservation of oocytes [2,5,7], IVF [3,8], intracytoplasmic sperm injection (ICSI) [5,6,9] and interspecies SCNT [10] have been conducted in Common minke (Balaenoptera acutorostrata) and Antarctic minke (B. bonaerensis) whales. Recently, we attempted for the first time to produce embryos of sei (B. borealis) whales by IVF of IVM oocytes in a research based ship [11].…”
mentioning
confidence: 99%
“…In those studies, 15-20% fetal whale serum was incorporated into the IVM media with osmolarity of approximately 310 mOsm, but the IVM media was not supplemented with whale follicular fluid (wFF). Iwayama et al [4,5] added 10% or 50% wFF to IVM media for fresh or vitrified Antarctic minke whale oocytes and found that the duration of IVM culture could be shortened to 30-40 h. The osmolarity of wFF (387.9 ± 3.1 mOsm; n= 23 [4]) is higher than those of bovine and porcine FF (approximately 300 mOsm). Addition of 10% wFF to IVM medium and adjustment of the osmolarity t o 3 9 0 m O s m p r o v i d e s a b e t t e r a n d m o r e physiological environment for in vitro maturation of common minke whale oocytes, although the osmolarity of wFF in common minke whales has not been examined [5].…”
Section: Discussionmentioning
confidence: 99%
“…Addition of 10% wFF to IVM medium and adjustment of the osmolarity t o 3 9 0 m O s m p r o v i d e s a b e t t e r a n d m o r e physiological environment for in vitro maturation of common minke whale oocytes, although the osmolarity of wFF in common minke whales has not been examined [5]. Iwayama et al [4] reported that IVM medium containing 50% wFF resulted in a similar proportion (approximately 30%) of matured oocytes after IVM culture for 28-30 h compared with the previous studies using 96-120 h [1][2][3]. The present study compared two durations of IVM culture (30 or 40 h) using medium supplemented with 10% wFF for common minke whale oocytes and found that 40 h of IVM culture was superior to 30 h in terms of the proportion of in vitro matured oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, 15-20% fetal whale serum was incorporated into IVM media with an osmolarity of approximately 310 mOsmol. Iwayama et al [4,27] added 10 or 50% wFF into IVM media for fresh or vitrified Antarctic minke whale oocytes, and found that the IVM duration could be greatly shortened to 30-40 h. The osmolarity of wFF (387.9 ± 3.1 mOsmol; n=23, [4]) is higher than those of bovine and porcine FF (approximately 300 mOsmol: unpublished data, Iwayama H.). Addition of 10% wFF to IVM medium adjusting the osmolarity to 390 mOsmol provides a better and more physiological environment for maturation of Antarctic minke whale oocytes in vitro [4,5,27].…”
Section: Discussionmentioning
confidence: 99%